The rituals of medicine : exploring the General Practice Consultation using simulated consultations - Arnet, Hayley Ruth (Curtin University, 2012)
The consultation is a distinguishing feature of general practice compared to other medical disciplines. The relationship between the doctor and patient is crucial to the successful outcome of the consultation. Despite suggestions in the literature that interruptions to the consultation are detrimental to this relationship, there is a lack of research to support this claim.The overall aim of this study was to explore the consulting style of General Practitioners (GPs) and the impact of interruptions to the consultation to further understand GP behaviour and the doctor-patient relationship during the consultation. The implication of the study was to raise awareness for GPs of their consulting style and interaction with patients, potentially leading to changes in behaviour, resulting in better outcomes from consultations.This research involved six GPs consulting six actor-patients during two video recorded simulated consultation workshops. This research consisted of three studies. The first involved observation of GP behaviour during the simulated consultations, and the impact of interruptions to the consultation; the second involved GP and patient perceptions of behaviour during the consultations, and the impact of the interruptions; and the third involved obtaining GP and patient perspectives of behaviour and interruptions to the consultations, prompted by video footage from the consultations.In Study 1, evidence was found to support a GP consultation style whereby individual GPs showed similar behaviours during each consultation despite consulting a variety of patients. Variability in GPs ability to cope with interruptions to the consultation, and the little time spent by GPs establishing a relationship with patients regardless of the consultation being interrupted was highlighted. The findings of Study 2 supported previous reports of the frequent occurrence of interruptions to the consultation. Differences between GPs beliefs and patient perceptions of the impact of interruptions to the consultation to the doctor-patient relationship were highlighted. In Study 3, the opening sequence of the consultation was found to be of importance to the doctor-patient relationship and the outcome of the consultation.Overall, the findings of this study showed GPs inability to describe their behaviour, and a lack of awareness of their behaviour during the consultation. As a result, GPs may be missing vital cues from patients during the consultation regarding their thoughts and concerns, which may have negative consequences for the doctor-patient relationship. These implications, however, require further research. This study concluded that reflection, and mindfulness could be applied to GP consultation behaviour, using video techniques, in order to raise GP self- awareness of behaviour, improve communication, and the way that GPs relate to patients, and to improve outcomes of general practice consultations.